Cross-border cooperation in the tri-national region of Iguassu: report of the municipal plan for international relations of Foz do Iguaçu, Paraná, Brazil - Oliveira Vieira, Gustavo; Péres de Oliveira, Suellen Mayara; Abu Ali, Jihad Ahmad (Revista Española de Desarrollo y Cooperación, 2022)
The present article aims to present some initiatives developed in the city of Foz do Iguaçu (Brazil), in a cooperation between local administration and university in order to promote the cross-border cooperation in the triple border region, linked with Puerto Iguazu (Argentina) and Ciudad del Este/Presidente Franco/Hernandarias (Paraguay) - the most populated border in South America. For such a purpose, the essay first presents the city and the region’s cross-border elements and its historical development, the potential of paradiplomacy to, in the sequence, report the efforts to create the Foz do Iguaçu International Relations Plan.